Production of Nanostructured Silver from Waste Radiographic Films Using a Microwave-Assisted Hydrothermal Method - Sa, Bruna S. [UNESP]; Zito, Cecilia A. [UNESP]; Perfecto, Tarcisio M. [UNESP]; Volanti, Diogo P. [UNESP] (Springer, 2018)
Radiographic films, widely used in medical and dental diagnosis, are an excellent source of silver (Ag), due to their content of light-sensitive Ag compounds. After their use, the films are commonly incorrectly thrown away in the regular trash, causing potential environmental damage. Thus, sustainable methods for recovering Ag from discarded radiographic films are desirable for economic reasons and environmental preservation. In this study, we performed the Ag recovery from waste radiographic films and carried out its structural, chemical, and morphological characterization. First, a solution of commercial bleach, based on sodium hypochlorite (NaClO), was used to separate Ag from radiographic films. Then, a microwave-assisted hydrothermal method was applied to produce nanometric metallic Ag using sucrose as a green reductant and sodium hydroxide (NaOH). The obtained product was composed of relatively high purity (similar to 97%) nanostructured Ag (NS-Ag). Thus, the proposed procedure was efficient, and a promising approach for Ag recovery from radiographic films since the obtained NS-Ag might be used in a wide range of technological applications.
Keywords: Silver recovery; Nanohydrometallurgy; Sustainability; Radiographic plate; Green reductant